Mechanisms that link circadian preference to problematic smartphone and social media use in young adults - Wallinheimo, Anna-Stiina; Evans, Simon L. (PLOS ONE, 2025)
Evening-types are at higher risk of problematic smartphone use and addiction to social media, but little is known about the possible mediating factors. Given the rising prevalence and broad negative impacts of smartphone and social media addiction, these factors require identification. Young adults (N = 407) aged 18–25, with an average age of 19.8 years, completed a battery of validated measures online. We tested mental health (anxiety and depression symptoms), loneliness, and poorer sleep quality as potential mediators in the relationships between eveningness and problematic smartphone use and social media addiction. As expected, evening types had higher prevalence of problematic smartphone use and social media addiction. Eveningness was also associated with higher anxiety and depression symptoms, loneliness, and poorer sleep quality. Two separate parallel mediation analyses were then conducted, with these three factors entered simultaneously as mediators. For problematic smartphone use, a partial mediation occurred, with loneliness as the significant mediating variable. For social media addiction, both loneliness and anxiety were significant mediators, and a full mediation was found. These important findings point to loneliness and anxiety as crucial explanatory variables for problematic technology use in young adults, suggesting that young adult evening types resort to smartphone/social media use as a dysfunctional coping strategy for loneliness and anxiety. Given the prevalence of problematic smartphone use and social media addiction amongst young people worldwide, and their wide-ranging negative impacts, this has important implications for prevention and intervention strategies to enhance young adults’ mental health, functioning, and well-being.